Nasal irrigation for the prevention and treatment of upper respiratory tract infection by SARS-CoV-2: a narrative review - Song Li; Xi-Cai Sun; Zhong-Fei Wu; Li Hu; Jing-Jing Wang; Min Yin; Lei Cheng; De-Hui Wang (Journal of Infection in Developing Countries)
Introduction: The World Health Organization declared an end to the global emergency status of COVID-19 in May of 2023. However, the impact of COVID-19 is far from over. Individuals who have recovered from COVID-19 continue to experience physiological, psychological, or cognitive symptoms, such as fatigue, shortness of breath, dizziness, and loss of smell or taste, known as long COVID. This review aims to describe the clinical characteristics of the upper respiratory tract infection (URTI) caused by SARS-CoV-2, and provide evidence for the prevention and treatment of SARS-CoV-2 infection by using nasal irrigation.